(untitled) (International Journal of Physiology, 2020)
Aim: The aim of the study is to assess blood pressure variation in different phases of menstrual cycle Objectives: To investigate any changes in blood pressure during different phases of menstrual cycle using mercury sphygmomanometer. Material and Method: 30 apparently healthy female medical students aged between 18-23 years were selected for the study and blood pressure was recorded by auscultatory method using mercury sphygmomanometer during the different phase of menstrual cycle as follows: a)Menstrual phase(MP) (2nd day) b)Proliferative phase(PP) (11th day) c)Secretory phase(SP) (22nd day). Results: Statistical analysis was done using SPSS 17.0 Software. To compare means of two independent groups, students t- test for independent samples was used. There was no significant difference in both systolic and diastolic blood pressure among different phases of the menstrual cycle Conclusion: There was no significant difference in both systolic and diastolic blood pressure among different phases of the menstrual cycle. These findings should be re-examined with a larger study group.